Energy flow structure and role of keystone groups in shallow water environments in Isla del Coco, Costa Rica, Eastern Tropical Pacific - Fourriére, Manon (2019)
Isla del Coco (Costa Rica) forms part of the five oceanic islands of the Eastern Tropical Pacific and is well known for its high biodiversity and great endemism. While several marine biological and oceanographical surveys have been conducted around the island over the past 35 years, an integrated, systematic view of the shallow water system is lacking as is an assessment of the impact of illegal fisheries. The aim of the study was thus to identify the main biological compartments of the Isla del Coco system and to quantify its energy flow structure through the development of a trophic model for the shallow water environments (≤30 m). With the software Ecopath with Ecosim, and based on the model structure previously used for Darwin and Wolf islets in the Galápagos Archipelago, a trophic model was developed using information from several field surveys and additional data from similar systems. The total biomass of the Isla del Coco system (1,972.25 t km−2) was mainly comprised of high trophic level species such as hammerhead shark, pelagic predatory fish and other sharks. The reef ecosystem is in a healthy (relatively undisturbed) state and dominated by large apex predators and mesopredators. Of the keystone groups identified (toothed cetaceans, tiger sharks, other sharks, benthic omnivorous fish and pelagic predatory fish), toothed cetaceans and tiger sharks were identified as having the strongest influence on the structure and diversity of the community through direct and indirect interactions. The Isla del Coco ecosystem presents a higher biomass than a similar system in the Galápagos archipelago, likely due to lower fishing pressure and higher system maturity.